Education and nationalism: The discourse of education policy in scotland - Arnott, M; Ozga, J (2010)
The paper draws on critical discourse analysis to examine and discuss some of the key developments in the governing of education in Scotland since the election of the Scottish National Party (SNP) government in May 2007. It analyses these developments, drawing on a study of key policy texts and suggests that discourse analysis has much to contribute to the understanding of the governing strategy of the minority SNP administration as reflected in its education policy. We suggest that there is a self-conscious strategy of'crafting the narrative' of government that seeks to discursively re-position 'smarter Scotland' alongside small, social democratic states within the wider context of transnational pressures for conformity with global policy agendas. Thus the paper connects to current debates on the relationship between an emergent global education policy 'field' and the capacity of 'local' contexts to develop and sustain particular, embedded assumptions and practices. © 2010 Taylor and Francis.